"An act of geographical violence": Crime, literature, and the colonial compulsion. (March 2022) - Slavin, Molly
This article proposes the idea of the "colonial compulsion", or an impulse for completion, neatness, and order, and argues that this urge is a motor that drives much literature that focuses on crime and cartography. Through readings of Brian Friel's play Translations (1980) and Paul Haworth's novel Only Killers and Thieves (2018), I make the case that crime narratives and depictions of mapping share the same root, that we read and enjoy crime stories for the same reason we find maps satisfying: because we wish to "solve" the crime in the same way we wish to see the "blank spaces" of the map inked in. "An act of geographical violence" holds that the type of contemporary literature which ties together cartography, crime, and colonialism urges the reader to think through and against colonial and modern-day systems of oppression. Ultimately, this article puts forth a sustained case for performing readings that deliberately intertwine the subjects of crime, cartography, and colonialism and for seriously examining the framework of the colonial compulsion.